Radical treatment of hepatic hydatidosis: Total adventicectomy - Torterolo, Edgardo; Vergara, Mirtha; Covic, Vida; Leites, Alejandro; Aizen, Bernardo; Czarnevicz, Daniel; Ferreira, Carlos; Palacios, José L; Peyroulou, Alfredo; Perrier, José P; et al. (Cirugía del Uruguay, 1994)
The authors analyse 121 patients that underwent total adventitectomy out of a total of 193 treated for hydatidosis between 1979 and 1990. They analyse indications, preoperative preparation, and technical aspects of the resection aswe/1 as morbimortality. Global mortality was 2.4%. lt is concluded that total ativentitectomy is an excellent procedure that prevents the serious posoperative complications of conservative procedures and adventitial disease.